2013
DOI: 10.1108/14777261311321798
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable structures for neighbourhood development?

Abstract: Even though many evaluations have been conducted to capture the process of interventions, little attention has been given to the challenges facing the outcomes of the intervention when it comes to making permanent the activities for reducing health inequalities. This paper is an attempt to deal with these challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Studies in other cities have also shown that urban communities in cities are facing different health challenges. Besides, their capacities for implementing the health city project are also highly varied [ 31 , 32 ]. This tendency was reflected by the various information-seeking behaviors in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other cities have also shown that urban communities in cities are facing different health challenges. Besides, their capacities for implementing the health city project are also highly varied [ 31 , 32 ]. This tendency was reflected by the various information-seeking behaviors in this study.…”
Section: Discussionmentioning
confidence: 99%